Autoimmune Gastritis Treated With Mycophenolate Mofetil. Issue 12 (9th December 2020) - Harb, Ali H.; Vemulapalli, Roopa; Gopal, Purva; Park, Jason Y.
ABSTRACT: Autoimmune gastritis is an inflammatory condition of the gastric mucosa. We report a 64-year-old woman with chronic abdominal pain of 3-year duration. Endoscopic and histologic evaluation revealed autoimmune pangastritis. The gastritis was partially responsive to steroids but attempts to taper failed, and the patient had no relief from mercaptopurine, adalimumab, budesonide, or hydroxychloroquine. The patient was treated with mycophenolate mofetil which resulted in resolution of symptoms. Endoscopic and histologic examination after mycophenolate therapy showed near complete resolution of active inflammation. To the best of our knowledge, this is the first report of symptomatic autoimmune gastritis successfully treated by mycophenolate mofetil.